People’s Consultation on Post-tsunami RRR in Sri Lanka - Dissanayake, Lakshman; Kaluthantiri Weeratunga, Manori (My University, 2005)
A greater part of post-tsunami relief, reconstruction and rehabilitation (RRR) work in Sri Lanka has been carried out by government structures ad international and local organizations alike with little emphasis participation. The initial lapses in this regard can be written-off against the sheer magnitude on the disaster; all actors sacrificed participatory processes in order to meet urgent recovery needs on the ground. Information-sharing between local communities and recovery agents is vital for ensuring the success and sustainability of the tsunami recovery process in Sri Lanka. On one hand, it prevents systematic discrepancies between relief, rehabilitation and reconstruction efforts and their corresponding needs on the ground. On the other hand, it builds ownership and trust in tsunami recovery and restores faith in the democratic process. This paper will attempt to share the experiences gained by attempting to strengthen capacities for tsunami recovery by: Carrying consultations at village-level in the tsunami-affected areas to ascertain the needs of the affected; disseminating information on tsunami-related issues and decisions to the affected communities and disseminating the findings of these consultations with policy-makers.
Keywords: People’s Consultation on Post-tsunami RRR in Sri Lanka